The Influence of Social Quality and Time Management on Increasing Learning Interest with Independent Behavior as a Moderator - Muhammad Junaid Kamaruddin (Economic, Management, Business and Accountancy International Journal, 2024)
The purpose of this study was to test and analyze the effect of time use and quality of association on study interest and independent behavior regulation as moderation. The sample in this study consisted of 157 respondents who were students from different universities. Respondent coverage is based on Hair's approach. The data collection technique used simple random sampling by distributing research questionnaires in Google format and then sharing them on social media. The data processing method of this study uses Smart PLS (Partial Least Square) software which is used for hypothesis testing. The results showed that the quality of association has a positive and significant effect on interest in learning, the use of time has a positive and significant effect on interest in learning, independent behavior has a positive and significant effect on interest in learning, independent behavior is proven to have a significant effect and can moderate the effect of the quality of association on interest in learning, and independent behavior is proven to have a significant effect and can moderate the effect of time management on interest in learning. recommend to students if they want to increase their interest in learning. Recommendations to students if they want to increase their interest in learning, it is advisable to be able to further improve the quality of association and time management, because some respondents of this study stated that in increasing student interest in learning, students must be able to maintain the quality of association and time management properly in order to increase interest in learning. students are also expected to be able to maintain good independent behavior, so that students can increase their interest in learning.